Commensal Microbiota Regulate Vertebrate Innate Immunity-Insights From the Zebrafish - Murdoch, Caitlin C.; Rawls, John F. (Frontiers in Immunology, 2019)
Microbial communities populate the mucosal surfaces of all animals. Metazoans have co-evolved with these microorganisms, forming symbioses that affect the molecular and cellular underpinnings of animal physiology. These microorganisms, collectively referred to as the microbiota, are found on many distinct body sites (including the skin, nasal cavity, and urogenital tract), however the most densely colonized host tissue is the intestinal tract. Although spatially confined within the intestinal lumen, the microbiota and associated products shape the development and function of the host immune system. Studies comparing gnotobiotic animals devoid of any microbes (germ free) with counterparts colonized with selected microbial communities have demonstrated that commensal microorganisms are required for the proper development and function of the immune system at homeostasis and following infectious challenge or injury. Animal model systems have been essential for defining microbiota-dependent shifts in innate immune cell function and intestinal physiology during infection and disease. In particular, the zebrafish has emerged as a powerful vertebrate model organism with unparalleled capacity for in vivo imaging, a full complement of genetic approaches, and facile methods to experimentally manipulate microbial communities. Here we review key insights afforded by the zebrafish into the impact of microbiota on innate immunity, including evidence that the perception of and response to the microbiota is evolutionarily conserved. We also highlight opportunities to strengthen the zebrafish model system, and to gain new insights into microbiota-innate immune interactions that would be difficult to achieve in mammalian models.